Kajian Ekonomis Penyelesaian Sengketa Bisnis melalui ADR (Alternative Despute Resolution) - Miswardi Miswardi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Â In line with the increasing demands of the business in the era of globalization, especially related to the resolution of business conflicts, business people have tried to find alternative dispute resolution methods other than justice. This is because the judicial institution as a legal institution that should be able to play its role in efforts to resolve various kinds of business conflicts, is in reality not as expected by business people. There is support for normative formalities. Therefore alternative dispute resolution institutions can be used as a very possible choice. This alternative institution is considered more effective in various aspects of business dispute resolution, in response to the demands of very fierce business competition. Some economic benefits gained from choosing a solution through ADR (Alternative Despute Resolution) are that this model is not formal, saves more time and also minimize costs in dispute resolution.Â